Purinergní P2X rodina a specifické vlastnosti P2X7 podtypu - Jindřichová, Marie; Zemková, Hana (Československá fyziologie, 2013)
Purinergic P2X receptors (P2XR), activated by extracellular adenosine 5‘-triphosphate (ATP), represent a specific type of li- gand-gated ion channels. They form functional trimeric homomers or heteromers which are nonselectively cation-perme- able after receptor activation. P2X receptors are widely expressed in excitable and nonexcitable tissues and are involved in many physiological and pathophysiological processes such as platelet aggregation, contraction of smooth muscle, immu- ne responses, cell proliferation and apoptosis or neurotransmission. In mammals, seven P2X subunits (P2X1-P2X7) have been identified. They differ mainly in distribution, pharmacological profile and kinetics of ATP-induced responses. The sub- type P2X7 is the most specific in the P2X family and widely differs from other P2X subtypes.
Keywords: mezibuněčné signální peptidy a proteiny; Purinergic P2X Receptor Agonists; extracelulární ATP; Receptors, Purinergic P2X7; extracelulární prostor; purinergní receptory P2X7; Receptors, Purinergic P2X; Signal Transduction; Humans; buněčná proliferace a apoptóza; purinergní receptory P2X1; Receptors, Purinergic P2X4; purinergní receptory P2X4; adenosintrifosfát; Adenosine Triphosphate; Extracellular Space; proliferace buněk; lidé; apoptóza; Receptors, Purinergic P2X1; purinergní receptory P2X; purinergní P2X rodina; signální transdukce; Cell Physiological Phenomena; fyziologie buňky; purinergní receptory P2X3; Intercellular Signaling Peptides and Proteins; Cell Proliferation; Apoptosis; agonisté purinergního receptoru P2X; Receptors, Purinergic P2X3